An Expression Signature as an Aid to the Histologic Classification of Non-Small Cell Lung Cancer - Girard, Luc (Clin Cancer Res, 2016)
PURPOSE: Most non-small cell lung cancers (NSCLCs) are now diagnosed from small specimens, and classification using standard pathology methods can be difficult. This is of clinical relevance as many therapy regimens and clinical trials are histology dependent. The purpose of this study was to develop an mRNA expression signature as an adjunct test for routine histo-pathological classification of NSCLCs. EXPERIMENTAL DESIGN: A microarray dataset of resected adenocarcinomas (ADC) and squamous cell carcinomas (SCC) was used as the learning set for an ADC-SCC signature. The Cancer Genome Atlas (TCGA) lung RNAseq dataset was used for validation. Another microarray dataset of ADCs and matched non-malignant lung was used as the learning set for a Tumor vs. Nonmalignant signature. The classifiers were selected as the most differentially expressed genes and sample classification was determined by a nearest distance approach. RESULTS: We developed a 62-gene expression signature that contained many genes used in immunostains for NSCLC typing. It includes 42 genes that distinguish ADC from SCC and 20 genes differentiating non-malignant lung from lung cancer. Testing of the TCGA and other public datasets resulted in high prediction accuracies (93–95%). Additionally, a prediction score was derived that correlates both with histologic grading and prognosis. We developed a practical version of the Classifier using the HTG EdgeSeq nuclease protection-based technology in combination with next-generation sequencing that can be applied to formalin-fixed paraffin-embedded (FFPE) tissues and small biopsies. CONCLUSIONS: Our RNA classifier provides an objective, quantitative method to aid in the pathological diagnosis of lung cancer.